PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DALAM KONTEKS PENDIDIKAN MODERN - Dodi Suhenda; Fokky Fuad; Pipyn Hidroga Sekti; Dede Syaefudin; Nia Sukmawati (Educatus, 2024)
Learning media is a central element in modern education, forming an integral part of dynamic and inclusive learning processes. Over time, learning media has undergone significant transformation from traditional forms to becoming more interactive, multimedia, and digital in line with advancements in information and communication technology. This research aims to examine the development of interactive learning media in response to the need for adaptive and technology-integrated learning approaches. The background of this study includes the increasing use of technology in education and the challenges faced in implementing relevant and effective learning media. The research methodology employed is a qualitative case study, involving analysis of the implementation of interactive learning media in secondary schools. The main findings indicate that the use of interactive learning media can enhance student engagement and facilitate collaborative learning. The implications of this research underscore the necessity for greater support in developing educational technology infrastructure in schools and providing training for educators to integrate technology into their teaching practices. The outcomes of this study are expected to provide guidance for policymakers and educational practitioners in leveraging technology effectively to enhance educational quality in the current digital era.